Nervus ischiadicus variations and clinical importance: A cadaver and MRI study - Tas, Ferhat; Ozbag, Davut; Ogeturk, Murat; Ozdemir, Zeynep Maras; Karatoprak, Nur Betul; Cevirgen, Furkan; Karatas, Turgay (Bayrakol Medical Publisher, 2025)
Aim: In this study, the variations, bifurcation levels, morphometric and topographic features of the ischiadicus nerve (NI), which has an important role in its protection, were investigated. Material and Methods: In eighteen cadaver limb dissections, variations related to NI and musculus piriformis (MP) and NI bifurcation levels, morphometric and topographic features of NI were investigated. At the foramen infrapiriforme (FI) exit, the distance between NI and trochanter major (TM), spina iliaca anterior superior (SIAS), crista iliaca (CI), spina iliaca posterior superior (SIPS), hiatus sacralis (HS) and tuber ischiadicum (TI) was measured. NI variations were investigated in 115 hip MRIs of 59 patients in the radiology archives. Results: No variation was encountered in NIs other than Type A, which is the most common and considered normal. In all lower extremities, it was observed that the NI bifurcated in the distal 1/3 of the thigh (Group E). FI-TM: 71 +/- 9.62 mm, FI-SIAS: 129.56 +/- 8.98 mm, FI-CI: 134.6 +/- 6.33 mm, FI-SIPS: 80.77 +/- 10.40 mm, FI-HS: 78.16 +/- 10.54 mm and FI-TI: 55.11 +/- 5.56 mm was found. 115 Magnetic resonance radiographs (MRI) showed Type B variation in 5 hips (4.34%) and Type A variation in the others (95.65%). Discussion: We think that our cadaver and MRI study can serve as a guide during clinical practice and will be useful in reducing NI injuries.
Keywords: Nervus Ischiadicus; Variation; Piriformis Syndrome; Cadaver; Magnetic Resonance Imaging